Aspek Romantisme Dalam Film Merindu Cahaya De Amstel - Hasni, Zulfa; Rasyimah, Rasyimah; Ginting, Reza Pahlevi (Kande : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study is entitled "Representation of Romanticism in the Film Merindu Cahaya De Amstel". The formulation of the research problem is how the representation of the aspect of romance is depicted in the film Merindu Cahaya De Amstel. The purpose of this study is to describe the representation of the aspect of romance in the film Merindu Cahaya De Amstel. The research approach used is a qualitative approach. Data collection techniques use listening techniques and note-taking techniques. The data source for this study is the film Merindu Cahaya De Amstel. The data in this study are in the form of dialogues and scenes that contain representations of aspects of romance in the film Merindu Cahaya De Amstel. The results of the study found that the representation of the romantic aspect of love is more dominant as a form of representation of romance in this film. The researcher found 14 data on representation of romance based on the aspect of love and 13 data on representation of romance based on the aspect of expression.